An Evaluation of Whitening Effect of Concentre Anti-Tache Nuit against Solar Simulated Radiation-Induced Delayed Tanning - Tezuka, Tadashi; Kawada, Akira; Shiraishi, Hatsuki; Aragane, Yoshinori; Asai, Mutsuyo (Skin research, 2001)
A new whitening cosmetic essence, ‘Concentre anti-tache nuit’(CAN)(Parfums Christian Dior), which contained 3% magnesium 1-ascorbyl 2-phosphate, vitamin A, andan antisense compound (DNA Na), was evaluated against solar simulated radiation-induced delayed tanning (DT) in the unexposed upper arm skin of 12 healthy Japanese females, aged20 to 55 years. Whitening effect was estimated by observation, photographs, and lightness at 6th week after-irradiation of single 3 minimal erythema dose. CAN demonstrated greater whitening effects on the applied area than the non-applied area in 10 of the 12 subjects (83%) with the combination of observation and photographs. Ten of 12 subjects showed the gap of lightness (L* value) more than 0.5 between the CAN- and non-application areas. There was a significantdifference of the absolute value of margin of L* from pre-irradiation site between CAN-applied and no-treatment areas. These results suggest that CAN has a whitening effect on solar simulated radiation-induced DT.